Strategies to Improve Probation Students’ Academic Performance in an American Degree Transfer Program (ADP) in Malaysia - Faizal, M.; Kalarani, V.; Sonya, P.; Eshodha, A. G.; Amirah, A. (International Journal of Engineering and Technology, 2018)
Students with poor academic performance for each academic semester were placed under academic probation program to monitor their progress. In previous studies, poor time management and the tendency to procrastinate were found to be the most significant factors that contributed to the student’s poor academic results. Other factors also include difficulties faced by students to cope with fundamental pre-requisite subject like mathematics. Therefore, this paper will focus on strategies to improve the students’ academic performance so that they will be out of the probation.